Determinan Perilaku Swamedikasi Penduduk Jawa Tengah - Utomo, Agung Priyo; Syahida, Inayati; Berliana, Sarni Maniar; Samosir, Omas Bulan; Sugiarto, Sugiarto (Jurnal Ekonomi Kependudukan dan Keluarga, 2024)
Self-medication has been practiced globally for thousands of years. As a part of primary healthcare services, self-medication forms the cornerstone of a sustainable healthcare system supporting universal health coverage, which is targeted in Sustainable Development Goal 3 (SDG 3), target 3.8. This study aims to provide an overview of self-medication behaviors and the factors influencing them among residents of Central Java Province. Using data from the 2021 National Socio-Economic Survey provided by the BPS-Statistics Indonesia, the sample size of this study includes 19,998 individuals, with 82.1% engaging in self-medication. The prevalence of self-medication is higher among males (84.0%) compared to females (80.6%). Self-medication is more common among individuals who are employed, live in rural areas, are unmarried, do not have health insurance, use the internet, are not poor, or have health complaints that do not interfere with daily activities, compared to their corresponding counterparts. The proportion of self-medication decreases with increasing age or higher education levels. Further binary logistic regression analysis identifies that the propensity for self-medication is higher among males (OR=1.16; 95% CI: 1.07-1.26), employed individuals (OR=1.40; 95% CI: 1.30-1.52), unmarried individuals (OR=1.17; 95% CI: 1.07-1.28), those without health insurance (OR=1.32; 95% CI: 1.20-1.44), the poor (OR=1.16; 95% CI: 1.02-1.31), those with health complaints that do not disrupt daily activities (OR=1.54; 95% CI: 1.43-1.66). The government needs to provide education and information regarding safe and responsible self-medication practices to at-risk groups, such as those with lower education levels, those without health insurance, and the poor, to maximize the benefits of self-medication and minimize the negative impacts of self-medication behaviors.